Chapter 4 The toll of totalising masculinities in prison - Symkovych, Anton (Taylor & Francis, 2023)
Gender relations implicate power and male privilege. Prisons largely house underprivileged men. How then do incarcerated men negotiate masculinities when gender relations in society-at-large, power relations inside prisons, and masculine ideas and ideals continue to change? Drawing on a semi-ethnographic study in a men's prison in Ukraine, I detail how the dynamic nature of gender normative ideals coexist with the more constant features of gender order: masculine surveillance, censure, and stratification. I highlight that notwithstanding the existence of alternative and subordinate masculinities, the power of hegemonic masculinities in prison is far from waning despite continuously shifting normative expectations and evolving masculine ideals. Whilst adding to the scholarship that questions the hypermasculine image of the men's prison world, this chapter, by foregrounding the costs men in prison bear in their daily struggle to attain and maintain masculine status, explains how men in prison are simultaneously victims and perpetrators of patriarchy.